Causality Evolution in Aristotelian and Avicennian Philosophy and Transcendent Wisdom - Mehraki, Bahador; Azimiyan, Abdolrasool (Technium BioChemMed, 2022)
The main questions raised in the present article include “What are common grounds and differences between Aristotle, Avicenna and Mulla Sadra’s approaches to causality?” and “How do their approaches to cause and effect evolve?” As the research findings suggest, Aristotle introduced four causes, considering the universe to be eternal and regards the agency a notion uniquely restricted to the final cause. On the other hand, drawing on his knowledge of Islamic teachings, Avicenna supports the Aristotelian four causes in addressing the creation problem but departs from his views by raising the notion of efficient cause as the creative cause to explain the problem of creation. Mulla Sadra considers the principality of existence and its gradation in order to hypothesize causality as an existential affair and views the effect as related to the cause. One of the most significant results of the present study, which was carried out by adopting a descriptive-analytical methodology, is that over time and with the evolution of some philosophical issues, the status of cause has become richer and the status of effect has become more subtle. As a result, certain ambiguities regarding causality in doctrinal discussions have been addressed.